Omental Prolapse Through Vaginal Cuff Dehiscence - Jon Solberg; Karan Saravana (Clinical Practice and Cases in Emergency Medicine, 2022)
Case Presentation: A 31-year-old female presented to the emergency department with abdominal pain and a 15-centimeter bloody vaginal protrusion, which resulted during an attempted bowel movement. Reduction of the mass was unsuccessful, and the patient was taken to the operating room for examination. Discussion: In patients with a history of vaginal hysterectomy, the vaginal cuff can dehisce and abdominal contents may protrude through the vaginal canal. In this case presentation, the vaginal mass was found to be omental tissue, which could be mistaken for a prolapse of vaginal mucosa. Therefore, a proper pelvic exam is imperative, as prolapse through a cuff dehiscence can lead to severe complications.